Contemporary Legal Perspectives on Paternity and Their Intersection with Islamic Family Law: A Doctrinal Literature Synthesis - Alias, Muhammad Nazir; Hamid Al-Badi, Muhammad Hamad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract This study explores the complex interplay between Islamic jurisprudence and modern legal frameworks in the determination of paternity. It critically examines mechanisms for establishing paternity, such as civil registration, Deoxyribonucleic Acid (DNA) testing, acknowledgment, and court declarations, across various legal systems, including secular (e.g., France, and the United States of America (USA)), hybrid (e.g., Nigeria, Egypt and United Arab Emirates (UAE)), and religious or Sharia-based jurisdictions (e.g., Saudi Arabia and Iran). To achieve the objectives of this study, the doctrinal legal research approached is adopted. Through comparative analysis, the research identifies both points of convergence, such as the presumption of paternity in marriage, and areas of conflict, particularly the tension between DNA evidence and classical Islamic rules of lineage (nasab). Case studies from Egypt, Nigeria, Malaysia, and select non-Muslim countries with Muslim populations demonstrate how different systems balance religious, cultural, and scientific considerations. The study also engages with theoretical and normative reflections on the doctrinal challenges posed by scientific advances, the role of ijtihad, and the implications for identity and ethics in Muslim societies. It concludes by recommending integrative legal models that uphold religious principles while embracing legal certainty, and calls for interdisciplinary dialogue, legislative harmonization, and further research into reconciling traditional and contemporary norms in paternity law.